Prevalence and characterization of Salmonella among humans in Ghana. Issue 1 (December 2017) - Andoh, Linda; Ahmed, Shabana; Olsen, John; Obiri-Danso, Kwasi; Newman, Mercy; Opintan, Japheth; Barco, Lisa; Dalsgaard, Anders
Abstract Background Non-typhoidal Salmonella (NTS) is a public health problem worldwide and particularly in Africa with high disease burden. This study characterizedSalmonella isolates from humans in Ghana to determine serovar distribution, phage types, and antimicrobial resistance. Further, the clonal relatedness among isolates was determined. Methods One hundred and thirty-sevenSalmonella isolates (111 clinical and 26 public toilet) were characterized using standard serotyping, phage typing, and antimicrobial susceptibility testing methods. The molecular epidemiology of common serovars (Salmonella Typhimurium andSalmonella Enteritidis) was established by pulsed field gel electrophoresis (PFGE). Results Twenty-two serovars were identified withS . Enteritidis, S . Typhimurium, andSalmonella Derby as the most dominant. One hundred and twelve isolates showed resistance to more than one antimicrobial. Fifty-eight (n  = 58/112; 54.5%) strains were multi-resistant with low resistance to cephalosporins ceftazidime (8.0%), cefotaxime (4.5%), and cefoxitin (2.7%) with synergy to clavulanic acid indicating possible ESBLs. Isolates showed high resistance to trimethoprim (66.1%), tetracycline (61.6%), ampicillin (57.1%), sulfamethoxazole (46.4%), chloramphenicol (33.9%), and ciprofloxacin (25.0%). The most common resistance pattern of multi-resistant serovars was to ampicillin, chloramphenicol, sulphonamide, and trimethoprim.S . Enteritidis (18/43) strains reacted with typing phages but did not conform to any phage type with PT14B and PT4 as predominant definitive phage types. SixS . Typhimurium strains reacted but did not conform to any recognized phage type while seven were non-typable. The predominant definitive phage types were DT1 and DT22. PFGE patterns of humanS . Enteritidis were closely related to patterns of poultry isolates obtained in a previous study in Ghana. Conclusions Cephalosporin resistance is uncommon amongSalmonella from humans in Ghana. Poultry may be an important source of human salmonellosis. There is an urgent need for the implementation of routine surveillance of antimicrobial use and bacterial resistance among humans in Ghana.